COMPARATIVE STUDY ON NUTRITIONAL AND ANTI NUTRITIONAL COMPOSITION OF FRESH AND DRIED OKRA OBTAINED FROM GUSAU MARKET NIGERIA - Shaibu, Momoh; Clifford, Odenigbo C.; Abdulahi, S. A.; Dikko, A. M. (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
Okra or commonly known in its Latin as abelmoschus esculentus are one of the green vegetables that is most consumed around the world and is utilized as medicine. Due to post-harvest losses, inadequate storage facilities lead to customers losing fresh okra. Therefore, farmers use traditional drying preservation methods by utilizing solar heat. The research objectives is to identify and evaluate the antinutrient, mineral, and proximate compositions of fresh and dried okra obtained from Gusau Market in Nigeria. Researchers analyzed and compared the samples using standard analytical methods and statistical packages from IBM SPSS version 21. The analysis revealed that the fresh and dried okra samples had the following amounts of water, ash, protein, fiber, carbs, lipids, and total energy: 75.30-8.56%; 1.85-8.05%; 16.44-77.25%; 4.30-2.03%; 0.18-3.15%; 1.93-0.96%; and 56.11-325.76%. While concentrations of mineral elements of fresh and dried okra are 98.22-97.80; 5.45-4.45; 9.75-9.35; 78.52-69.35; 21.36-19.26; and 30.52-29.60 in mg/100g respectively. The phytochemical screening shows the presence of Tannin, Oxalate, Phytate, Saponin, Phenolic, Flavonoid and Alkaloid. For sampling of fresh and dried okra, the amounts of flavonoid and alkaloid in mg/100g are 18.6-17.95 and 10.64-15.14, respectively. There is no significance different in proximate, mineral elements and anti nutritional content between fresh and dried okra samples. Therefore, the researchers can decide that the traditional way by utilizing solar heat is still being utilised by most of farmers. The appropriate method for farmers to prevent lossing okra when post-harvest is having conducive environment for them in order to avoid possible contamination.